A comparison of hole-filling methods in 3D - Pérez, Emiliano; Salamanca, Santiago; Merchán, Pilar; Adán, Antonio (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a review of the most relevant current techniques that deal with hole-filling in 3D models. Contrary to earlier reports, which approach mesh repairing in a sparse and global manner, the objective of this review is twofold. First, a specific and comprehensive review of hole-filling techniques (as a relevant part in the field of mesh repairing) is carried out.
Keywords: survey; 3D polygonal models; repairing meshes; hole-filling; restoration algorithms